# Calc.

posted by Derek

What function would have a derivative of ƒ′(x) = 12x2 + 4x − 10? Explain how you arrived at your answer...I believe the answer is this: f(x)=4x^3+2x^2-10x...and I got this using the power rule and multiplying. Thanks.

1. drwls

Your answer is correct. You can add an arbitrary constant to it for the general answer, which is called the indefinite integral. Whatever method you used seems to work.

The integral or "antiderivative" of each term of the form
a x^n is a*x^(n+1)/(n+1)
Just add the different polynomial terms. That apparently is what you did.

## Similar Questions

1. ### PHY 2054

Use the relativistic coordinate transformation (x, y, z, t) − (x′, y′, z′, t′) shown and given below where the latter frame S′, (x′, y′, z′, t′), has a velocity 2.69813 × …
2. ### College Physics

Use the relativistic coordinate transformation (x, y, z, t) − (x′, y′, z′, t′) shown and given below where the latter frame S′, (x′, y′, z′, t′), has a velocity 2.69813 × …
3. ### Derivatives- Math

Can someone explain how to find the derivative of : 1. y= 5^ãx / x And the second derivative of: y= xe^10x For this question I got up to the first derivative and got this y = e^10x + 10xe^10x but I can't seem to get the correct …
4. ### math

Estimate f′(−3) where f(x) = x^3 + 8x^2 − 10x − 1 to within one decimal place by using a small enough interval. f′(−3) ≈
5. ### Calc

I'm creating a "calculu for dummies" project book. I've already done most of it, I'm just stuck on these ones. Thank you! -What is the definition of a derivative?
6. ### math

I have the same project as Jill down there... -What is the definition of a derivative?
7. ### calculus

i need to find the derivative using chain rule: (x^2 + 2x - 6)^2 (1-x^3)^2 i got the answer from a site but the problem is i cannot get my work to match up with the answer, i don't know what im doing wrong. answer: 10x^9 + 36x^8 − …
8. ### Calculus

Given f(x)=−2x^3 -3x + 1, the value of the derivative of the inverse function, f^−1(x) at x=−21 is (f^1)′(−21)= ?
9. ### Calc 1

G(X) = x^2(1-2x) I have to differentiate this function I used the power and product rule G'(X)= (x^2)'(1-2x)+(x^2)(1-2x)' I got down to 2x-4x+(x^2)(-2x) 2x-6x^2 which is the answer but what do info with the extra x^2?
10. ### Math- Calc

Suppose f(5)=5, f′(5)=5, g(5)=8, g′(5)=−8, and H(x)=f(x)e^(g(x)). Find the derivative (dH)/(dx) x=5. H′(5)= ___

More Similar Questions